Progress of photoacoustic imaging combined with targeted photoacoustic contrast agents in tumor molecular imaging - Zheng, Yiwen; Liu, Mengyao; Jiang, Lixin (Frontiers in Chemistry, 2022)
Molecular imaging visualizes, characterizes, and measures biological processes at the molecular and cellular level. In oncology, molecular imaging is an important technology to guide integrated and precise diagnosis and treatment. Photoacoustic imaging is mainly divided into three categories: photoacoustic microscope, photoacoustic tomography and photoacoustic endoscope. Different from the traditional imaging technology, which uses the physical properties of tissues to detect and identify diseases, photoacoustic imaging uses the photoacoustic effect to obtain the internal information of tissues. During imaging, endogenous or exogenous photoacoustic contrast agents are excited by laser and generate ultrasonic signals. At present, photoacoustic imaging combined with targeted photoacoustic contrast agents has been widely used in the study of tumor molecular imaging. In this review, we will focus on the recent development of photoacoustic imaging technology and targeted photoacoustic contrast agents, as well as the research progress in the field of tumor molecular imaging.